Analisis Terhadap Tindak Pidana Perdagangan Satwa Liar yang Dilindungi Studi Putusan Pengadilan Negeri Bantul - Widodo Widodo; Francisca Romana Harjiyatni (Kajian Hasil Penelitian Hukum, 2019)
One of the main factors that threatens the extinction of animals is hunting for trade. Various types of protected and endangered animals are still being traded, one of them is in Bantul. In fact, there are already rules prohibiting the trade in protected animals, which are regulated in Law Number 5 of 1990 concerning the Conservation of Biological Resources and their Ecosystems. This study aims to determine a criminal trade in protected wildlife that exists in the Bantul district court's law regarding judges' considerations in deciding cases of protected wildlife trade and what are the obstacles faced by judges in imposing prison sentences on protected animal trade.This research uses a literature study in the form of decisions in the Bantul District Court and is strengthened by interviews with judges who decide cases. The approach in this study uses descriptive analytic. Based on the results of data analysis and research that has been done, that the sentencing of judges at the Bantul District Court in 2016 to 2017 has been based on the evidence and beliefs of judges in the form of animals and information from various witnesses presented at the trial. As for the judge's conviction, it is based on the conditions that exist in the community regarding the crime case of protected wildlife trade. The fall of the judge's verdict in the Bantul District Court has several obstacles, namely the lack of cases of trade in protected animals, and case files and attachments that have not been well prepared by other institutions so the trial lasts long.